Pengaruh Consumer Review terhadap Keputusan Pembelian pada E-commerce Shopee, Indonesia - Mochamad Fali Septokasya (Asosiasi Ahli Administrasi Indonesia, 2024)
Consumer reviews play a very important role in purchasing decisions on e-commerce platforms. In today's digital era, many buyers rely on reviews from other consumers to assess the quality of a product before deciding to buy. This study aims to analyze the influence of consumer reviews on purchasing decisions on the Shopee e-commerce platform, especially among students in the Greater Bandung area. The method used is a quantitative approach with a descriptive survey of 112 respondents with simple linear regression analysis. The results of the study indicate that consumer reviews have a significant effect on purchasing decisions. These findings provide insight for business actors, especially in the e-commerce sector, to utilize consumer reviews as an effective marketing strategy, by creating and maintaining positive reviews to increase consumer trust and encourage purchasing decisions.